Defining the role of Interleukin-6 for the development of perioperative neurocognitive disorders: Evidence from clinical and preclinical studies - Barreto Chang, Odmara L.; Maze, Mervyn (Frontiers in Aging Neuroscience, 2023)
For most, staying “mentally sharp” as they age is a very high priority that may be thwarted by the consequences of a postoperative complication unrelated to the disorder which necessitated the surgical intervention. Perioperative neurocognitive disorder (PND) is an overarching term for cognitive impairment in surgical patients, that includes conditions from delirium to dementia, affecting more than 7 million patients annually in the US, and which threatens both functional independence and life. Clinical trials and meta-analyses have identified the association between PNDs and increased perioperative levels of interleukin-6 (IL-6), a pleiotropic cytokine that is both necessary and sufficient for postoperative memory decline in a preclinical model of PND. Recently, we reported that, in adult male wild-type mice subjected to tibial fracture under general anesthesia, IL-6 trans-signaling in hippocampal CA1 neurons mediates surgery-induced memory impairment. As there are no therapeutic options for preventing or reversing PNDs, patients and their caregivers, as well as the healthcare industry, endure staggering costs. Olamkicept, a highly selective IL-6 trans-signaling blocker has shown to be efficacious and safe in clinical trials involving patients with inflammatory bowel disease, another condition for which IL-6 trans-signaling is the mediating mechanism. Subject to a demonstration that olamkicept is effective in preventing cognitive impairment in vulnerable (aged and Alzheimer’s Disease) preclinical PND models, clinical trials involving aged and/or cognitively impaired surgical patients should be undertaken to study olamkicept’s utility for PNDs.